Global fractional anisotropy and mean diffusivity together with segmented brain volumes assemble a predictive discriminant model for young and elderly healthy brains: a pilot study at 3T - Garcia-Lazaro, Haydee Guadalupe; Becerra-Laparra, Ivonne; Cortez-Conradis, David (My University, 2016)
Several parameters of brain integrity can be derived from diffusion tensor imaging. These include fractional anisotropy (FA) and mean diffusivity (MD). Combination of these variables using multivariate analysis might result in a predictive model able to detect the structural changes of human brain aging.Our aim was to discriminate between young and older healthy brains by combining structural and volumetric variables from brain MRI: FA, MD, and white matter (WM), gray matter (GM) and cerebrospinal fluid (CSF) volumes.This was a cross-sectional study in 21 young (mean age, 25.71±3.04 years; range, 21-34 years) and 10 elderly (mean age, 70.20±4.02 years; range, 66-80 years) healthy volunteers. Multivariate discriminant analysis, with age as the dependent variable and WM, GM and CSF volumes, global FA and MD, and gender as the independent variables, was used to assemble a predictive model.The resulting model was able to differentiate between young and older brains: Wilks’ λ = 0.235, x2 (6) = 37.603, p =.000001. Only global FA, WM volume and CSF volume significantly discriminat- ed between groups. The total accuracy was 93.5%; the sensitivity, specificity and positive and negative predictive values were 91.30%, 100%, 100% and 80%, respectively.Global FA, WM volume and CSF volume are parameters that, when combined, reliably discriminate between young and older brains. A decrease in FA is the strongest predictor of membership of the older brain group, followed by an increase in WM and CSF volumes. Brain assessment using a predictive model might allow the follow-up of selected cases that deviate from normal aging. © 2016, CIC Edizioni Internazionali s.r.l. All rights reserved.
Keywords: Aging; Brain; Diffusion tensor imaging; Discriminant analysis; Volume; White matter